ATTEMPTS TO REFORM THE ADMINISTRATIVE-TERRITORIAL STRUCTURE OF UKRAINE (1990-2012) - Адамович, С. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The articles analyses and evaluates the attempts to reform the administrative-territorial structure of Ukraine in 1990-2012. The author argues that the administrative-territorial reform hit upon the absence of political will of the top political authorities of Ukraine, lack of necessary funding and resistance of the regional elites.